Volatile and carbohydrate composition of rare unifloral honeys from Spain - Delafuente, E.; Sanz, M.; Martinezcastro, I.; Sanz, J.; Ruizmatute, A. (Food Chemistry, 2007)
Volatile composition and carbohydrate content of Spanish honey samples from uncommon botanical origins have been studied by gas chromatography coupled to mass spectrometry. About 100 volatile compounds were identiﬁed; some of them appeared to be characteristic of particular honey types, such as methyl salycilate in willow (Salix spp.), 2,6,6-trimethyl-2,4-cycloheptadien-1-one (eucarvone) in almond tree (Prunus dulcis) and isophorone in strawberry-tree (Arbutus unedo). Concentration ranges for major carbohydrates were similar to those previously reported in other honeys with diﬀerent botanical origins, although concentrations of maltulose in avocado honeys (Persea americana) and of melezitose in Quercus ilex honeys were higher. Some carbohydrate alcohols could also be considered as markers of honey botanical origin, such as quercitol for Q. ilex and perseitol for avocado.
Keywords: carbohydrates; gc; GC-MS; honey; ms; polyalcohols; volatile compounds

Carbon and nitrogen winter storage and remobilisation during seasonal flush growth in two-year-old cork oak (Quercus suber L.) saplings - Cerasoli, Sofia; Maillard, Pascale; Scartazza, Andrea; Brugnoli, Enrico; Chaves, Maria Manuela; Pereira, João Santos; Erasolia, Sofia C.; Aillardc, Pascale M.; Cartazzad, Andrea S.; Rugnolid, Enrico B.; Havesa, Maria Manuela C.; Ereiraa, João Santos P. (Ann. For. Sci., 2004)
A dual long-term 13C and 15N labeling was used to assess the contribution of winter assimilated carbon (C) and nitrogen (N) for the spring growth flush of two-year-old cork oak plants. Changes in concentrations and partitioning of winter assimilated C and N, total C and N, and total-non-structural carbohydrates were followed from January to August in the various plant parts (first year and second year leaves, stem, branches, coarse and fine roots). No loss of winter C and N was observed with time suggesting that winter assimilates are retained within the plant and contribute to storage. A strong mobilisation of C and N was demonstrated from first year leaves and fine roots during the spring growth flush. Leaves from the second year and, to lesser extent, branches acted as sinks for winter C and N. At the beginning of the new leaf growth, a significant decrease in starch concentration occurred in first year leaves. In August, before leaf fall we observed also a mobilisation from first year to second year leaves, of N assimilated after labeling. We conclude that under these experimental conditions, both winter and current C and N were used for the spring growth flush of the cork oak plants. The foliage grown during the previous year was a source of winter and recently assimilated N and a source of C from recent assimilates for the new growth in the spring.
Keywords: 13C labeling; 15N labeling; carbohydrates; Quercus suber; remobilisation